2015
DOI: 10.1016/j.kjms.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Propofol target‐controlled infusion for sedated gastrointestinal endoscopy: A comparison of propofol alone versus propofol–fentanyl–midazolam

Abstract: Gastrointestinal (GI) endoscopy is the major technique for diagnosis of GI disease and treatment. Various sedation and analgesia regimens such as midazolam, fentanyl, and propofol can be used during GI endoscopy. The purpose of the study was to compare propofol alone and propofol combination with midazolam and fentanyl in moderate sedation for GI endoscopy. One hundred patients undergoing GI endoscopy were enrolled in this study. All patients received a propofol target-controlled infusion (TCI) to maintain sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…Previous studies have shown that propofol has early awakening and recovery compared to thiopentone, midazolam. 6,9,10 In our study also, both groups achieved preoperative finger tapping score and visual-spatial memory by 2 hr. Young et al and Shukry et al, showed that intraoperative dexmedetomidine effectively reduced the incidence and intensity of emergence agitation without prolonging recovery and discharge time.…”
Section: Figure 4 Discussionsupporting
confidence: 72%
“…Previous studies have shown that propofol has early awakening and recovery compared to thiopentone, midazolam. 6,9,10 In our study also, both groups achieved preoperative finger tapping score and visual-spatial memory by 2 hr. Young et al and Shukry et al, showed that intraoperative dexmedetomidine effectively reduced the incidence and intensity of emergence agitation without prolonging recovery and discharge time.…”
Section: Figure 4 Discussionsupporting
confidence: 72%
“…Of 10 studies that compared arrhythmia rates, four studies reported the rate of bradycardia . The combined results showed no evidence for a difference (RR, 1.59; 95% CI, 0.75 to 3.35; P chi 2 = 0.042; I 2 = 44.59%; NNTH = 386.3; 95% CI, NNTH 25.6 to ∞ to NNTB 29.5).…”
Section: Resultsmentioning
confidence: 95%
“…A retrospective analysis showed that a triple sedation regimen (midazolam + fentanyl + propofol) provided safety and reduced dosage of sedatives [6]. Our previous study in sedative gastrointestinal endoscopy also revealed less recovery time in patients who received the triple regimen (midazolam+ fentanyl+ propofol) [12].…”
Section: Discussionmentioning
confidence: 97%
“…One systemic review study suggested dexmedetomidine exerts potential benefits over midazolam in procedural sedation [10]. However, these sedatives alone often provide insufficient sedative or analgesic effects as well as delayed recovery [11][12][13], for which previous studies suggest a combined sedative/analgesic regimen improve efficacy and safety during endoscopic examination [14][15][16].…”
Section: Introductionmentioning
confidence: 99%